IMPORTANCE- PERFORMANCE ANALYSIS IN PHARMACY DEPARTEMENT OF PKU MUHAMMADIYYAH HOSPITAL, BANTUL (ACCORDING TO OUTPATIENTS PERCEPTION) - Yenita Malasari; Ibnu Gholib Gandjar; Sumarni Sumarni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Hospitals which are engaged in services, not only serve the sick people but must also consider aspects of customerssatisfaction. This research aims to determine whether it is the characteristic of patient that causing significant differenceon their satisfaction, to determine service attribute which require attention in order to service improvement towardscustomers, and to determine the gap between service quality with patient satisfaction in Pharmacy Department PKU Muhammadiyah Bantul hospital from the dimensions of SERVQUAL: reliability, responsiveness, assurance, empathy, and tangible.The research was designed by non experimental methods. Samples of this research are customers or families ofpatiens or outpatients taking drug at Pharmacy Department PKU Muhammadiyah Bantul hospital. Conveniencesampling is used as sampling method with number of samples 100 persons. Questioners are used as data collectionmethod taken on August 2009.The results showed that there is no significant difference between patient characteristic on patient satisfactionin Pharmacy Department PKU Muhammadiyah Bantul hospital. Attributes that become top priority to improvingservice quality are the friendliness and courtesy of employee, quick to follow up issues, and availability of thenumber and types of drugs. There are gaps in most of the service quality attributes in Pharmacy Department PKUMuhammadiyah Bantul hospital. The biggest gap is drug delivery information, employee knowledge, and patienslead time. Key words: Service quality, satisfaction, SERVQUAL dimensions, pharmacy department PKU Muhammadiyah Bantul Hospital